A View from the Inside: The Dawning Of De-Westernization of CEE Media and Communication Research? - Lauk, Epp (2015)
The Editorial outlines some characteristics of the development of the Central and Eastern European (CEE) media and communication scholarship during the past 25 years. In the majority of CEE countries, the media and communication research was re-established after the collapse of communism. Since then, a critical mass of active scholars has appeared who form an integral part of the larger European academia. A gradual integration of East and West perspectives in media and communication research is taking place along with moving away from the barely West-centred approach, and utilizing the research done by CEE scholars. Certain ‘de-westernization’ and internationalization of the research in terms of theoretical and methodological frameworks is depicted.